A novel method to characterize morphological dynamics and determine flashing jet regimes. (March 2021) - Song, Zeyang; Mei, Yu; Zhu, Xueliang; Ma, Jiajia; Pan, Xuhai; Jiang, Juncheng
Highlights: A novel method is proposed to depict nonlinear boundary of expansion zone. The method is validated by observations on images and comparison with spray angle. Graphical parameter k proposed by the novel method unifies a cluster of spray angles. k owns a good capability to characterize morphological dynamics of flashing jet. A prototype of k -value criteria for determining flashing jet regimes is developed. Abstract: Spray cone angle ( θ ) and width ( H ) have been widely used to characterize morphology of jets. However, to a flashing jet, their capabilities are restrained by two flaws: (a) they are variable as a function of axial distance ( θ ( H )= f ( x )), leading to nonunified θ or H at different axial locations, and (b) fail to precisely capture key characteristics of nonlinear boundary of expansion zone, resulting in their disability to determine the flashing jet regimes. In this work, a power function | y |= kx 0.5, in which x and y are axial and radical directions respectively, characterizing the nonlinear boundary of expansion zone of flashing jet is proposed. A variety of experiments are conducted to validate the proposed method. Experimental results demonstrate that the graphical parameter k unifies a cluster of spray angles ( θ = f ( x ))), and furthermore, owns a good capability to characterize morphological dynamics of flashing jet. These merits allow k to determine the flashing jet regimes. In this work, k <1, 1< k <5, and k >5 are the determining criteria for the external, internal transition, and full flashing jet regimes, respectively. Graphical abstract: Image, graphical abstract